Ladle slag line repairing material and preparation method thereof

By using raw materials such as magnesium sand, post-use magnesium carbon brick powder, combined with ultrafine graphite powder and other additives, the adhesion and high temperature resistance of the laminate slag line repair material are improved, and the poor construction performance and adhesion performance of the existing repair material are solved. The problem of instability extends the service life of the ladle slag wire.

CN119490346AActive Publication Date: 2025-02-21武汉钢铁有限公司

Patent Information

Application Number
CN202411700905.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-21
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing ladle slag line repair materials have poor construction performance, unstable adhesion performance, easy to decline overall, and have a high rebound rate, and are prone to fall off locally after baking. The water-based repair materials have high moisture content and a long construction period, which affects the service life of magnesium-carbon bricks. .

Method used

Magnesium sand, magnesium carbon brick powder after use, iron and phosphorus powder, etc. are used as the main raw materials, combined with ultrafine graphite powder, pig iron particles, kaolin fine powder and spherical SiO2 micro powder, etc., to wrap magnesium sand and ultrafine graphite powder through liquid oil, adjust The fluidity, plasticity and viscosity of the repair material improve adhesion performance.

Benefits of technology

It significantly improves the high temperature resistance and adhesion properties of the repair material, extends the service life of the ladle clamp wire, shortens the repair period, and reduces pollution to high-quality molten steel.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a ladle slag line repairing material which comprises the following components in percentage by mass: 60-85% of magnesia, 5-15% of used magnesia carbon brick powder, 2-11% of iron phosphorus powder, 0.3-2% of metal aluminum powder, 2-6% of superfine graphite powder, 2-8% of pig iron particles, 1-10% of kaolin fine powder and 1-5% of spherical SiO2 micro powder. And 2-20% of additional waste engine oil, 0-16% of aluminum dihydrogen phosphate and 0.2-0.6% of amine-terminated polyisobutene are further included. The steel ladle slag line repairing material has good high temperature resistance and adhesion performance, the adhesion effect on a steel ladle slag line can be effectively improved, the service life of the steel ladle slag line can be prolonged, and the steel ladle slag line repairing material is wide in applicability; and the related preparation method is relatively simple and relatively short in period, can realize resource utilization of various solid and liquid wastes, and has remarkable economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steelmaking and refractory materials, and particularly relates to a ladle slag line repairing material and a preparation method thereof. Background Art

[0002] The ladle is one of the important equipment required for the steelmaking process. In addition to being used for the storage and transportation of molten steel, it also participates in the refining and other process treatments of molten steel. Improving the service life of the ladle is conducive to improving the production efficiency of the steel plant, reducing energy consumption, saving resources and reducing environmental pollution. Among them, during the use of the ladle, the slag line is eroded by slag and the radiation of the electric arc during the smelting process of the ladle furnace. The erosion rate is the fastest, which is the bottleneck of the service life of the ladle lining. In order to avoid the replacement of the entire working lining due to local damage to the ladle lining and extend the service life of the ladle working lining, it is necessary to repair the ladle slag line working lining with repair materials.

[0003] At present, the working layer of the domestic ladle slag line mostly uses magnesia carbon bricks. Conventional high-aluminum water-based ladle repair materials usually have poor construction performance, some of which have unstable adhesion performance, are easy to slide down as a whole, and have a high rebound rate; some parts are easy to fall off after baking. The water-based repair material has a high water content, and the construction, maintenance and baking cycles are long. In addition, the moisture will also cause certain damage to the magnesia carbon bricks. These are all unfavorable to the use of the repair material and the ladle slag line after the repair material. Summary of the invention

[0004] The main purpose of the present invention is to provide a ladle slag line repair material to address the problems and shortcomings of the prior art, which can improve the high temperature resistance and adhesion performance of the repair material, effectively improve the adhesion effect on the ladle slag line and extend the service life.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A ladle slag line repair material, the components and their mass percentages include: 60-85% magnesia sand, 5-15% used magnesia carbon brick powder, 2-11% iron phosphorus powder, 0.3-2% metal aluminum powder, 2-6% ultrafine graphite powder, 2-8% pig iron particles, 1-10% kaolin fine powder, 1-5% spherical SiO2 micropowder; also includes waste engine oil added and accounting for 2-20% of the total mass of the above raw materials, 0-16% of aluminum dihydrogen phosphate and 0.2-0.6% of terminal amino polyisobutylene.

[0007] In the above scheme, the magnesia comprises magnesia aggregate particles of 1-5 mm and magnesia fine powder with a particle size less than 200 mesh, wherein the MgO content is ≥94wt%.

[0008] Furthermore, in the magnesia, the content of magnesia aggregate particles is above 55wt%.

[0009] In the above scheme, the spent magnesia carbon brick powder is recovered from the spent magnesia carbon bricks in the converter or ladle, and the carbon content of the original brick is ≥10wt%; and the MgO content is ≥60wt%.

[0010] In the above scheme, the particle size of the iron phosphorus powder is less than 180 mesh, it is recycled from rolled steel phosphorus, and the TFe content is ≥70wt%.

[0011] In the above solution, the particle size of the ultrafine graphite powder is less than 2000 mesh.

[0012] In the above scheme, the particle size of the pig iron particles is 1-3 mm.

[0013] In the above scheme, the particle size of the kaolin fine powder is less than 300 mesh

[0014] In the above scheme, the spherical SiO2 powder has a particle size less than 2000 mesh.

[0015] In the above scheme, the waste oil needs to be filtered and purified, and the solid impurity content cannot exceed 0.5wt% and the water content does not exceed 0.5%.

[0016] In the above scheme, the molecular weight of the amine-terminated polyisobutylene is 400-1200.

[0017] The above-mentioned method for preparing a ladle slag line repair material comprises the following steps:

[0018] 1) Add the ultrafine graphite powder weighed according to the proportion into the waste oil to which the amino-terminated polyisobutylene has been added, stir and disperse evenly, then add all the magnesia aggregate, stir and disperse evenly, and seal;

[0019] 2) At the repair construction site, add the remaining dry materials (used magnesia carbon brick powder, iron phosphorus powder, metal aluminum powder, pig iron particles, kaolin fine powder, spherical SiO2 powder) and aluminum dihydrogen phosphate according to the proportion and mix and stir evenly before use for repair construction.

[0020] Furthermore, by adjusting the ratio of kaolin fine powder and spherical SiO2 micropowder, the fluidity and plasticity of the obtained repair material can be effectively controlled, among which, when the mass ratio of kaolin fine powder and spherical SiO2 micropowder is 1:2-3, the repair material has better fluidity; when the mass ratio of kaolin fine powder and spherical SiO2 micropowder is 2-3:1, the repair material has better plasticity; the viscosity of the material is adjusted by adjusting the amount of aluminum dihydrogen phosphate added; the fluidity of the repair material is adjusted by adjusting the amount of waste engine oil added; the temperature of the repair material after construction can be controlled by changing the amount of pig iron added, and combined with the adjustment of the fluidity of the repair material, the performance of the repair layer adhering to steel slag at the desired position can be controlled, and steel slag can be adhered to protect the repair layer as needed.

[0021] The ladle slag line repair material obtained by the above scheme is applied to the repair of the ladle slag line or other parts of the furnace lining using magnesia carbon bricks. Specifically, the ladle slag line repair material can be set at the part to be repaired by applying or self-flowing means to form a repair layer.

[0022] Furthermore, the ladle slag line repair material can be applied in a cold state or repaired by a self-flowing process in a hot state (800-1200° C.).

[0023] The principle of the present invention is:

[0024] The present invention uses magnesia, used magnesia-carbon brick powder and iron-phosphorus powder as main raw materials to prepare ladle slag line repair material. In order to reduce the adverse effect of high carbon content of the material on the quality of molten steel, firstly, ultrafine carbon raw material (ultrafine graphite powder) is mixed in liquid grease through a super dispersant to improve its dispersion uniformity and help reduce the amount of carbon raw material added; the magnesia raw material is pre-wrapped with liquid grease to avoid the influence of hydration of magnesia on the performance of the repair material; and kaolin fine powder, spherical SiO2 micropowder and pig iron particles are combined to adjust the fluidity, plasticity and surface temperature of the repair layer after construction, so as to control the ability of the repair material to adhere to steel slag. Steel slag can be adhered to the surface of the repair layer as needed to protect the repair layer, thereby further improving the repair life.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1) The ladle slag line repair material of the present invention has good high temperature resistance and adhesion performance, which can effectively improve the adhesion effect on the ladle slag line and extend its service life.

[0027] 2) The present invention can adjust the fluidity, plasticity and viscosity of the repair material according to the on-site needs of the damaged area and severity of the ladle slag line to meet different repair construction requirements such as self-flowing pouring at high temperature or coating in cold state; while ensuring the repair effect, it can effectively shorten the repair period and increase the service life of the ladle slag line.

[0028] 3) The present invention can regulate the surface temperature of the repair layer after the repair material is constructed, control the performance of the repair layer in adhering to steel slag, and further effectively adhere steel slag to the surface of the repair layer according to actual needs to protect the repair material and further improve the repair life.

[0029] 4) The present invention mixes ultrafine graphite powder in liquid grease under the action of terminal amino polyisobutylene, which can effectively reduce the amount of carbonaceous raw materials added and reduce the pollution to high-quality molten steel; at the same time, premixing magnesia into liquid grease can avoid hydration of magnesia and increase the shelf life of the repair material. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with specific embodiments. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.

[0031] In the following embodiments, the raw materials used in the ladle slag line repair material include, by weight percentage: 55-75% magnesia sand, 5-15% used magnesia carbon brick powder, 0-11% iron phosphorus powder, 0.5-2% metallic aluminum powder, 2-6% ultrafine graphite powder, 2-6% pig iron particles, 2-10% kaolin fine powder, 1-4% spherical SiO2 micropowder; 2-20% waste engine oil; 0-16% aluminum dihydrogen phosphate; and 0.2-0.6% terminal amino polyisobutylene.

[0032] In the following examples, the magnesia raw materials used are mainly aggregate particles with a particle size of 1-5 mm and fine powder with a particle size less than 200 mesh; wherein the content of the magnesia aggregate particles is ≥50wt%.

[0033] The spent magnesia carbon brick powder is recovered from the spent magnesia carbon bricks in the converter or ladle, and the original brick carbon content is 12.7wt%, and the MgO content is 66.2wt%. The iron phosphorus powder is recovered from the rolled steel phosphorus and crushed to a particle size of less than 180 mesh.

[0034] The particle size of the ultrafine graphite powder used is less than 2000 mesh; the particle size of the pig iron particles is 1-3mm; and the particle size of the kaolin fine powder is less than 300 mesh.

[0035] The waste oil used must be filtered and purified, and the solid impurity content cannot exceed 0.5%, and the water content cannot exceed 0.5%.

[0036] The molecular weight of the amine-terminated polyisobutylene used is 400-1200.

[0037] When preparing the repair material, ultrafine graphite powder is added to the waste engine oil to which terminal amino polyisobutylene has been added, and stirred and dispersed evenly, and then all the fine powder of magnesia sand particles is added and stirred evenly, and then sealed and packaged in a container; at the repair construction site, the remaining dry materials (used magnesia carbon brick powder, iron phosphorus powder, metal aluminum powder, pig iron particles, kaolin fine powder, spherical SiO2 micropowder) and aluminum dihydrogen phosphate are added according to the ratio and mixed and stirred evenly before use for repair construction. The fluidity, plasticity and adhesion of the repair material can be adjusted by the ratio of engine oil and aluminum dihydrogen phosphate, and the repair construction method can adopt cold coating or hot self-flowing process.

[0038] Example 1

[0039] A ladle slag line repair material, the raw materials used and the mass percentages thereof are: 55% of magnesia particles, 16% of magnesia fine powder, 14% of used magnesia carbon brick powder, 0.5% of metal aluminum powder, 3.5% of ultrafine graphite powder, 2% of iron phosphorus powder, 2% of pig iron particles, 2% of kaolin fine powder, 5% of spherical SiO2 micro powder; 2% of waste engine oil, 0.2% of terminal amino polyisobutylene, and 16% of aluminum dihydrogen phosphate;

[0040] The preparation method of the ladle slag line repair material comprises the following steps:

[0041] First, add the ultrafine graphite powder into the waste engine oil to which the terminal amino polyisobutylene has been added, stir and disperse evenly, then add the magnesia particles and magnesia fine powder, stir evenly, and seal and package in a container; at the repair construction site, add the remaining dry materials and aluminum dihydrogen phosphate according to the ratio and mix and stir evenly.

[0042] After testing, the obtained repair material has high fluidity at room temperature and can meet the requirements of self-flowing casting. It has moderate plasticity and adhesion. The shell surface temperature of the obtained repair material after solidification on the ladle lining surface is about 30-50℃ lower than that of ordinary repair materials. The compressive strength at 110℃×24h is 28.6MPa, and the compressive strength at 1500℃×3h is 57.3MPa. The self-flowing repair method is suitable for repairing large-area local damage of the ladle slag line or large repair thickness under cold state.

[0043] Example 2

[0044] A ladle slag line repair material, the raw materials used and the mass percentages thereof are: 55% of magnesia particles, 12% of magnesia fine powder, 9% of used magnesia carbon brick powder, 0.5% of metal aluminum powder, 3.5% of ultrafine graphite powder, 4% of iron phosphorus powder, 4% of pig iron particles, 3% of kaolin fine powder, 9% of spherical SiO2 micro powder; 6% of waste engine oil, 0.3% of terminal amino polyisobutylene, and 9% of aluminum dihydrogen phosphate;

[0045] The preparation method of the ladle slag line repair material comprises the following steps:

[0046] First, add the ultrafine graphite powder into the waste engine oil to which the terminal amino polyisobutylene has been added, stir and disperse evenly, then add the magnesia particles and magnesia fine powder, stir evenly, and seal and package in a container; at the repair construction site, add the remaining dry materials and aluminum dihydrogen phosphate according to the ratio and mix and stir evenly.

[0047] After testing, the obtained repair material has low fluidity at room temperature, high plasticity and adhesion. The shell surface temperature of the obtained repair material after solidification on the ladle lining surface is about 50-80℃ lower than that of ordinary repair materials; the compressive strength at 110℃×24h is 25.7MPa, and the compressive strength at 1500℃×3h is 52.4MPa. The repair method of smearing is suitable for local damage repair of small area of ​​ladle slag line or small repair thickness under cold state.

[0048] Example 3

[0049] A ladle slag line repair material, the raw materials used include, by weight percentage: 60% magnesia particles, 4% magnesia fine powder, 12% used magnesia carbon brick powder, 11% iron phosphorus powder, 2% metal aluminum powder, 5% ultrafine graphite powder, 2% pig iron particles, 1% kaolin fine powder, 3% spherical SiO2 micro powder; 16% waste engine oil; 0.6% terminal amino polyisobutylene;

[0050] The preparation method of the ladle slag line repair material comprises the following steps:

[0051] Add the ultrafine graphite powder into the waste engine oil to which the terminal amino polyisobutylene has been added and stir to disperse evenly, then add the magnesia particles and magnesia fine powder and stir to evenly, and finally add the remaining dry materials and mix and stir to evenly.

[0052] After testing, the obtained repair material has high fluidity at high temperature (1000℃). The shell surface temperature of the obtained repair material after solidification on the ladle lining surface is about 30-50℃ lower than that of ordinary repair materials. The compressive strength at 1500℃×3h is 29.5MPa. It adopts the self-flowing repair method in hot state and is suitable for repairing large-area local damage of the ladle slag line or large repair thickness in hot state.

[0053] Example 4

[0054] A ladle slag line repair material, the raw materials used include, by weight percentage: 56% magnesia particles, 4% magnesia fine powder, 13% used magnesia carbon brick powder, 8% iron phosphorus powder, 2% metal aluminum powder, 5% ultrafine graphite powder, 6% pig iron particles, 2% kaolin fine powder, 4% spherical SiO2 micro powder; 12% waste engine oil; 0.4% terminal amino polyisobutylene;

[0055] The preparation method of the ladle slag line repair material comprises the following steps:

[0056] Add ultrafine graphite powder to waste engine oil and stir to disperse evenly, then add fine magnesia powder and stir to evenly, and finally add the remaining dry materials and mix and stir to evenly.

[0057] After testing, the obtained repair material has high fluidity at high temperature (1000℃), and the compressive strength at 1500℃×3h is 24.2MPa. It adopts the self-flow repair method in hot state, which is suitable for repairing severe local damage of the ladle slag line in hot state. The shell surface temperature of the obtained repair material after solidification on the ladle lining surface is 150-200℃ lower than that of ordinary repair materials, which can reduce the fluidity of some steel slag components with lower melting points when solidified on the surface of the repair material shell, so that the repair material has a higher slag sticking ability, which can provide additional protection for the slag line.

[0058] Other implementation examples fluctuate within this range. The present invention is not limited to the above-mentioned implementations. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention. Contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A ladle slag line repair material, characterized in that: The components and their mass percentages include: 60-85% magnesia sand, 5-15% used magnesia carbon brick powder, 2-11% iron phosphorus powder, 0.3-2% metal aluminum powder, 2-6% ultrafine graphite powder, 2-8% pig iron particles, 1-10% kaolin fine powder, and 1-5% spherical SiO2 micropowder; and also include waste engine oil, which accounts for 2-20% of the total mass of the above raw materials, 0-16% of aluminum dihydrogen phosphate, and 0.2-0.6% of terminal amino polyisobutylene.

2. The ladle slag line repair material according to claim 1, characterized in that: The magnesia comprises magnesia aggregate particles of 1-5 mm and magnesia fine powder with a particle size less than 200 meshes, wherein the MgO content is ≥94wt%.

3. The ladle slag line repair material according to claim 1, characterized in that: In the magnesia, the content of magnesia aggregate particles is more than 55wt%.

4. The ladle slag line repair material according to claim 1, characterized in that: The MgO content in the used magnesia carbon brick powder is ≥ 60wt%.

5. The ladle slag line repair material according to claim 1, characterized in that: The particle size of the iron-phosphorus powder is less than 180 meshes, and the TFe content is ≥70wt%.

6. The ladle slag line repair material according to claim 1, characterized in that: The particle size of the ultrafine graphite powder is less than 2000 meshes; the particle size of the kaolin fine powder is less than 300 meshes; and the particle size of the spherical SiO2 micropowder is less than 2000 meshes.

7. The ladle slag line repair material according to claim 1, characterized in that: The particle size of the pig iron particles is 1-3 mm.

8. The ladle slag line repair material according to claim 1, characterized in that: The waste engine oil has a solid impurity content of less than 0.5 wt % and a water content of less than 0.5 wt %.

9. The ladle slag line repair material according to claim 1, characterized in that: The molecular weight of the amine-terminated polyisobutylene is 400-1200.

10. The method for preparing the ladle slag line repair material according to any one of claims 1 to 9, characterized in that: The steps include: 1) Add the ultrafine graphite powder weighed according to the proportion into the waste oil to which the amino-terminated polyisobutylene has been added, stir and disperse evenly, then add magnesium sand, stir and disperse evenly, and seal; 2) Add used magnesia carbon brick powder, iron phosphorus powder, metal aluminum powder, pig iron particles, kaolin fine powder, spherical SiO2 fine powder and aluminum dihydrogen phosphate according to the proportion, mix and stir evenly to obtain the ladle slag line repair material.

Citation Information

Patent Citations

  • Phenolic resin containing nano-carbon powder, nano-carbon modified low carbon magnesium carbon brick and production method thereof

    CN101220195A

  • Repair material for bottom of combined blowing converter

    CN110092643A

  • High-quality RH gunning mix added with large amount of cast iron powder and production method thereof

    CN112479685A

  • Preparation method of refractory material for cement kiln firing zone

    CN113929438A

  • Pleonaste brick and preparation method thereof

    CN118771860A

Cited By

  • Calcium hexaaluminate repairing material as well as preparation method and application thereof

    CN120682040A